The Art of Goodbye: Why People Are Talking About the End of Life - Suzanna Smith; Lynda Spence (EDIS, 2016)
Mortality has been a taboo subject for many years. Many cultural, demographic, educational, and policy changes have played a part in a shift toward an increased openness to talking about death as a natural part of life in the United States. This 5-page fact sheet is the first publication in a series entitled The Art of Goodbye: End of Life Education series, and it covers changes in living and dying, preferences for the end of life, roles of substitute decision makers in health care, and communication. Written by Suzanna Smith and Lynda Spence, and published by the UF Department of Family, Youth and Community Sciences, October 2016.